Tempo oscillations in rhythmic human networks - Elad Shniderman; Maya Wertsman; Hadar Granot; Hamootal Duadi; Moti Fridman (Scientific Reports)
Abstract Understanding oscillatory behavior in human networks is essential for exploring synchronization, coordination, and collective dynamics. In this study, we investigate tempo oscillations in complex human networks using a system of coupled violin players with precisely controlled network parameters. Each player interacts via delayed auditory feedback, allowing us to explore the effects of connectivity, delay, and tempo on network oscillations. We identify two distinct types of oscillations: fast (2–3 s) and slow (5–25 s), and demonstrate that their periods are independent of network size and delay but are strongly correlated with the network’s average tempo. Additionally, we show that increasing the number of coupled neighbors enhances oscillation damping, indicating the role of connectivity in stabilizing network dynamics. By varying the delay rate, we discover a critical decay rate where oscillation amplitude transitions from damping to amplification. These results provide valuable insights into the dynamic interplay of tempo, delay, and connectivity in coupled oscillator systems, with implications for applications in group dynamics, distributed systems, and synchronization processes.